Development of stress-induced cardiomyopathy after cytoreductive surgery and hyperthermic intraperitoneal chemotherapy - Saad Ahmed Naved; Sadiq Shoukat Parpia; Huma Shoukat Ali (Journal of the Pakistan Medical Association, 2021)
Pseudomyxoma Peritonei, a massive mucinous peritoneal collection due to a rare epithelial neoplasm, can be effectively treated with Cytoreductive Surgery and Hyperthermic Intraperitoneal Chemotherapy (CRS-HIPEC). 43-year-old female, previously treated for mucinous ovarian carcinoma with CRS-HIPEC, Total Abdominal Hysterectomy and Bilateral Salpingo-Oophorectomy, presented with new-onset abdominal distension and early satiety. She was diagnosed with Pseudomyxoma Peritonei. After 48 hours of treatment with CRS-HIPEC, she presented hemodynamically unstable with acute chest pain. Electrocardiogram showed broad complex tachycardia with ST depression in leads V3-6. Severe systolic dysfunction with EF of 20% along with severe pulmonary hypertension was visualized on Echocardiography. A diagnosis of Stress-induced Cardiomyopathy was established using InterTAK Diagnostic Score. Patients with CRS-HIPEC have presented with Stress-induced Cardiomyopathy. However, no relation between the two has been established, specifically. Thus, this case report discusses Stress-induced Cardiomyopathy as a complication of CRS-HIPEC. Continuous...